Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.18632/oncotarget.27331
|View full text |Cite
|
Sign up to set email alerts
|

miR-151a enhances Slug dependent angiogenesis

Abstract: MicroRNAs (miRs) are small non-coding RNAs, that modulate cognate gene expression either by inducing mRNA degradation or by blocking translation, and play crucial and complex roles in tissue homeostasis and during disease initiation and progression. The sprouting of new blood vessels by angiogenesis is critical in vascular development and homeostasis and aberrant angiogenesis is associated with pathological conditions such as ischemia and cancer. We have previously established that miR-151a functions as an onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Importantly, this is distinct from vasculogenic mimicry, whereby tumor cells form “fluid-conducting networks” without, however, acquiring endothelial cell markers, such as CD31 [ 10 , 11 ]. Although some studies have linked the EMT-inducing transcription factors Twist and ZEB1 to vasculogenic mimicry [ 63 65 ], or Slug to angiogenesis [ 60 ], our data are consistent with a mechanism akin to EMT-associated dedifferentiation conferring enhanced cellular plasticity and endothelial differentiation potential. In support of this idea, cells that have undergone EMT acquire phenotypic markers of mature endothelial cells, notably the expression of CD31 and KDR, following culture in EGM-2.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Importantly, this is distinct from vasculogenic mimicry, whereby tumor cells form “fluid-conducting networks” without, however, acquiring endothelial cell markers, such as CD31 [ 10 , 11 ]. Although some studies have linked the EMT-inducing transcription factors Twist and ZEB1 to vasculogenic mimicry [ 63 65 ], or Slug to angiogenesis [ 60 ], our data are consistent with a mechanism akin to EMT-associated dedifferentiation conferring enhanced cellular plasticity and endothelial differentiation potential. In support of this idea, cells that have undergone EMT acquire phenotypic markers of mature endothelial cells, notably the expression of CD31 and KDR, following culture in EGM-2.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies demonstrated that the induction of EMT bestows stem-like capabilities upon differentiated epithelial carcinoma cells, exemplified by the acquisition of enhanced tumor-initiating potential and the capacity to differentiate into multiple mesodermal lineages in vitro [ 25 , 26 ]. A recent study showed that miR-151a enhances angiogenesis in normal lung tissue and non-small cell lung cancer 3D tumor spheroids by increasing the levels of the EMT-inducing transcription factor Slug [ 60 ]. However, a direct connection between the induction of EMT and the onset of angiogenesis has not yet been established in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, SLUG and SNAIL have been reported to inhibit each other in oral cancer [Nakamura et al, 2018] and breast cancer [Ganesan et al, 2015]. The effect of SLUG on EMP dynamics can also be influenced by upstream regulators of SLUG such as RNF8, YAP, C/EBPδ, miR-151, CBP, RCP, HDAC1, HDAC3, BRD4 and STAT3 [Cheng et al, 2020;Chesnelong et al, 2019;Kuang et al, 2020;Wang et al, 2020;Daugaard et al, 2017;Jury et al, 2020;Dai et al, 2020;Hwang et al, 2017;Hu et al, 2020;Shafran et al, 2020]. Moreover, SLUG may be involved in feedback loops with one or more p63 isoforms [Srivastava et al, 2018;Dang et al, 2016;Herfs et al, 2010] that can also enable a partial EMT [Jolly et al, 2017a;Westcott et al, 2020].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-4449 is significantly downregulated in superior and middle temporal gyrus extracts of AD cases [ 25 ], and even though the current study showed upregulation of this miRNA, its expression could vary depending on the tissue under study. Upregulation of miR-151a circulating levels is also observed in AD and ischaemic stroke patients [ 26 , 27 ] and has a role in the strengthening of the endothelial cell barrier in primary lung endothelial cells [ 28 ], suggesting it could also impact the BBB. Interestingly, miR-151a circulating levels vary with age [ 29 ] as well as with disease stage in amyotrophic lateral sclerosis (ALS) [ 30 ] and Parkinson’s disease (PD) [ 31 ], where mir-151a levels are downregulated at moderate and severe disease stages; studies in transgenic mouse models of AD have also shown age-dependent expression of miR-652-5p [ 32 ], and of miR-16-1-3p [ 33 ].…”
Section: Discussionmentioning
confidence: 99%